Prescription Practices of Cannabinoids in Children with Cerebral Palsy Worldwide-A Survey of the Swiss Cerebral Palsy Registry - Sandra Hunziker; Federico Morosoli; Kathrin Zuercher; Anne Tscherter; Sebastian Grunt (MDPI AG, 2023)
Cannabinoids are prescribed to children with cerebral palsy despite limited evidence. We aimed to assess cannabinoid prescribing practices in children with cerebral palsy, focusing on indications, types of preparations used, and tolerability. Furthermore, we investigated how physicians acquire knowledge about cannabinoid medication. We asked physicians with expertise in the care of children with cerebral palsy about their prescribing practices for cannabinoids. Data were collected through an online survey, which was distributed by email. In addition to the demographic information of participants, we also inquired about the indications for the prescription of cannabinoids, experiences regarding efficacy, and observed side effects of the therapy. Seventy physicians from Europe, North America, and Australia completed the survey. Forty-seven participants were experienced in treating of children with cerebral palsy with cannabinoids. The most common indication was epilepsy (69%), followed by spasticity (64%) and pain (63%). The preparations and doses prescribed varied considerably. Half of the participants evaluated the effect of the cannabinoids as moderate. Twenty-nine physicians reported side effects, most frequently, drowsiness (26%), somnolence (19%), fatigue (13%), and diarrhea (13%). Despite the lack of evidence to date, cannabinoids are used to treat children with cerebral palsy in a wide variety of indications. Randomized controlled trials in this vulnerable patient group are therefore of utmost importance.